A Note on the 25 Most Frequent Surnames from the 2000 United States Census Bureau List. (3rd July 2017) - Nuessel, Frank
Abstract : This note uses the United States Census Bureau database of the 1, 000 most frequent surnames from the US census of 2000. It discusses briefly the meaning and origin of the notion of surname. It provides a table of the 25 most frequent surnames in the US from the 2000 census data, including number of people with the surname, and its meaning. This article provides the reader with three useful onomastic research tools for surnames: (1) The US Census Bureau's list of the 1, 000 most frequently occurring surnames for 2000; (2) Patrick Hanks' Dictionary of American Surnames ; and (3) the National Geographic interactive surname list.